The influence of self-management on the mathematics learning outcomes of students - Sitompul, Fika Tio Menti Br; Siregar, Sakinah Ubudiyah; Pasaribu, Laili Habibah (Universitas Islam Negeri Raden Intan Lampung, 2025)
The purpose of this study was to analyze the effect of self-management on students' mathematics learning outcomes. This research is classified as a quantitative ex post facto type. The instrument used is a self-management questionnaire consisting of 20 statements, as well as odd semester report card data as an indicator to measure students' mathematics learning outcomes. The results of simple linear regression indicate that there is an influence of self-management on the mathematics learning outcomes of eighth-grade students at SMP Negeri 2 Rantau Utara.